Coin of China’s infant formulas: the challenge and chance - Lifang, Wu; Yuexin, Yang (Progress in Nutrition, 2014)
From 2000 to 2013, there were 16-18 million newborn and 48-52 million children aged 1-3 years every year in China. We estimated that about 40% of Chinese children younger than 3 years are formula fed...